The specificity of audio material and linguistic treatments in the radio drama Ex Barbie by Maciej Kowalewski - Matusiak, Eliza; Wypiorczyk, Agnieszka (Papers in Linguistics, 2020)
Narration is an immanent component of audio drama’s dramaturgy. The narrative specificity in audio play Ex Barbie by Maciej Kowalewski has a determined construstructure of the story in the phonic layer, which has to be coherent with the verbum layer. The main character’s creation and the narrative determines the shape of the story on the audio and diegetic levels. A fictional radio art is analyzed with radio studies methods, but rarely from the linguistic perspective. The author aims at indicating determinants of audio implementation in Ex Barbie and analyzing ways of accomplishing coherence in audio drama in interdisciplinary perspective of linguistic and radio studies. In addition, in the selected radio play authors have analyzed the characters’ phonic gestures.